Neutral atmosphere dynamics in the E- and F-regions from Fabry-Perot Doppler imaging observations - Kubota, Minoru; Okano, Shoichi; Fukunishi, Hiroshi (1998)
P(論文) In order to investigate a response of the thermospheric neutral winds to the auroral activity, we developed a Fabry-Perot Doppler Imaging System (FPDIS) which measures Doppler shifts and widths of aurora and/or airglow emission lines of OI557.7nm and OI630.0nm over a wide field of view (165°) to obtain twodimensional patterns of winds and temperatures in the E-and F-regions. We carried out the FPDIS observations at Syowa Station (69.00°S, 39.58°E), Antarctica over 57 nights covering the various auroral conditions in 1994. In this paper, we discuss the following results obtained from our observations : (1) We found that nighttime variations in the thermospheric neutral winds depend on geomagnetic activity. Magnetically southward winds during geomagnetically active periods were stronger than during quiet periods, and the difference in the wind velocities was largest around midnight. This difference is supposed to be associated with auroral energy injection and the relative location between the auroral oval and Syowa Station. (2) Periodic enhancements in meridional winds, which were classified into middle-scale atmospheric gravity waves (AGWs), were observed on the night of 3-4 June 1994 during geomagnetically active periods. These wind enhancements appeared to be generated in the auroral oval which remained at a few hundred kilometers north of Syowa Station. departmental bulletin paper